Autofluorescence and white light imaging‐guided endoscopic Raman and diffuse reflectance spectroscopy for in vivo nasopharyngeal cancer detection. Issue 4 (12th February 2018) - Lin, Duo; Qiu, Sufang; Huang, Wei; Pan, Jianji; Xu, Zhihong; Chen, Rong; Feng, Shangyuan; Chen, Guannan; Li, Yongzeng; Short, Michael; Zhao, Jianhua; Fawzy, Yasser; et al.
Abstract : Nasopharyngeal cancer (NPC) is an endemic with high incidence in Southern China and Southeast Asia countries. Screening for NPC under conventional white light imaging (WLI) nasopharyngoscope examination remains a great clinical challenge due to its poor sensitivity. Here, we developed an integrated 4‐modality endoscopy system combining WLI, autofluorescence imaging (AFI), diffuse reflectance spectroscopy and Raman spectroscopy technologies for in vivo endoscopic cancer detection for the first time. A pilot clinical test of the system for NPC detection was conducted, in which 283 in vivo Raman and diffuse reflectance spectral data sets from 30 NPC patients and 30 healthy subjects were acquired under the guidance of AFI and WLI. Both high diagnostic sensitivity (98.6%) and high specificity (95.1%) for differentiating cancer from normal tissue sites were achieved using this system combined with principal component analysis‐linear discriminant analysis diagnostic algorithm, demonstrating great potential for improving real‐time, in vivo diagnosis of NPC at endoscopy. Abstract : An integrated endoscopy system provides white light imaging, autofluorescence imaging, Raman spectroscopy and diffuse reflectance spectroscopy for in vivo nasopharyngeal cancer detection.